LU_GERICHTE 11 10 153 vom 19. August 2011 - LU Gerichte (2011)
Art. 3 Abs. 2, 738 Abs. 1 und 2 und 971 Abs. 1 ZGB. Inhalt einer Fahrwegdienstbarkeit und guter Glaube des Dritteigentümers. | Zivilrecht